Advertised meeting-the-competition clauses: Collusion instead of price discrimination - Oliver Budzinski; Jürgen-Peter Kretschmer (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2010)
Pricing strategies may include the advertising of meeting-the-competition clauses (MCCs). We show in a specific spatial model scenario with differently informed consumers that MCCs primarily serve as a device to facilitate collusion instead of allowing for price discrimination between these consumers.
Keywords: M21; M37; L40; L11; D21; 330; meeting-the-competition clauses; advertising; price discrimination; competition; collusion; Betriebliche Preispolitik; Werbung; Preisdifferenzierung; Kartellrecht; Theorie